Factors Related to Participation of BPJS Mandiri - Yesi Triantina; Atikah Adyas; Kodrat Pamudho (GLOBAL HEALTH SCIENCE GROUP, 2021)
Based on the data obtained from BPJS of Lampung Province in 2020, Tulang Bawang Barat Regency is the regency with the lowest number of BPJS participation in Lampung Province compared to 12 other regencies. The total number of BPJS Mandiri participants in 2020 was 45,738 people, which is still below the set target of 117,000 people. The purpose of this research is to determine the factors related to the participation of BPJS Mandiri in Tulang Bawang Barat Regency in 2021. The research is a quantitative descriptive type, with the research design in this research is analytic with a cross sectional approach. The population is 9,848 people, the sample size is 117, the sampling technique is stratified random sampling. The technique of collecting data on research variables about products, prices, distribution channels, promotions and membership of BPJS Mandiri in this study is filling out a questionnaire directly by respondents who are assisted by 5 enumerators, then after filling in the data directly collected on the same day. Univariate data analysis using percentage measures, bivariate analysis using chi square test and multivariate analysis using multiple logistic regression statistical tests. The results showed that the distribution of BPJS product frequency was higher in the poor category by 82 people (70.1%), BPJS prices were higher in the poor category by 84 people (71.8%), distribution channels were higher in the poor category by 68 people (58.1%), BPJS Mandiri promotion was higher in the poor category by 71 people (60.7%), BPJS Mandiri participation was higher in the category of non BPJS Mandiri participants by 60 people (51.3%). The results of the chi square test showed that there was a product relationship (p value = 0.009 < 0.05), there was a price relationship (p value = 0.001 < 0.05), there was no distribution channel relationship (p value = 0.542 > 0.05) and there is a promotion relationship (p value = 0.007 < 0.05) with BPJS Mandiri participation. Price variable is the most dominant variable related to BPJS Mandiri participation (p value = 0.019 < 0.05).